Pathophysiological Responses to Conotoxin Modulation of Voltage-Gated Ion Currents - Elisabetta Tosti; Raffaele Boni; Alessandra Gallo (Marine Drugs, 2022)
Voltage-gated ion channels are plasma membrane proteins that generate electrical signals following a change in the membrane voltage. Since they are involved in several physiological processes, their dysfunction may be responsible for a series of diseases and pain states particularly related to neuronal and muscular systems. It is well established for decades that bioactive peptides isolated from venoms of marine mollusks belonging to the Conus genus, collectively known as conotoxins, can target different types and isoforms of these channels exerting therapeutic effects and pain relief. For this reason, conotoxins are widely used for either therapeutic purposes or studies on ion channel mechanisms of action disclosure. In addition their positive property, however, conotoxins may generate pathological states through similar ion channel modulation. In this narrative review, we provide pieces of evidence on the pathophysiological impacts that different members of conotoxin families exert by targeting the three most important voltage-gated channels, such as sodium, calcium, and potassium, involved in cellular processes.